Crystallization and preliminary X-ray characterization of the full-length bacteriophytochrome from the plant pathogen Xanthomonas campestris pv. campestris - Klinke, Sebastián (International Union of Crystallography, 2014)

(untitled) (Acta Crystallogr F Struct Biol Commun)
Phytochromes give rise to the largest photosensor family known to date. However, they are underrepresented in the Protein Data Bank. Plant, cyanobacterial, fungal and bacterial phytochromes share a canonical architecture consisting of an N-terminal photosensory module (PAS2–GAF–PHY domains) and a C-terminal variable output module. The bacterium Xanthomonas campestris pv. campestris, a worldwide agricultural pathogen, codes for a single bacteriophytochrome (XccBphP) that has this canonical architecture, bearing a C-terminal PAS9 domain as the output module. Full-length XccBphP was cloned, expressed and purified to homogeneity by nickel–NTA affinity and size-exclusion chromatography and was then crystallized at room temperature bound to its cofactor biliverdin. A complete native X-ray diffraction data set was collected to a maximum resolution of 3.25 Å. The crystals belonged to space group P4(3)2(1)2, with unit-cell parameters a = b = 103.94, c = 344.57 Å and a dimer in the asymmetric unit. Refinement is underway after solving the structure by molecular replacement.